The Effect of Profitability and Good Corporate Governance Mechanisms on the Timeliness of Annual Financial Report Publication: An Empirical Study on the Infrastructure, Utilities, and Transportation Subsector Companies Listed on the Indonesia Stock Exchange for the period 2020 - 2022 - Trisna, Dinda Agung; Arum, Enggar Diah Puspa; Wijaya, Rico (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of profitability and the mechanism of Good Corporate Governance, as proxied by the independent board of commissioners, managerial ownership, and the audit committee, on the timeliness of annual financial report publication. The study uses companies from the infrastructure, utilities, and transportation sub-sectors listed on the Indonesia Stock Exchange for the period 2020-2022. The data analysis technique used is purposive sampling. The sample in this study consists of 27 companies. The data analysis technique used is multiple linear regression. The results of this study show that profitability and the independent board of commissioners do not affect the timeliness of the annual financial report publication. Managerial ownership and the audit committee do affect the timeliness of the annual financial report publication.